Pengembangan Multimedia Pembelajaran Interaktif Berbasis Articulate Storyline 3 Sebagai Upaya Peningkatan Motivasi Dan Prestasi Belajar IPA Siswa Kelas VI Sekolah Dasar - Fariz Budiarto; Akhmad Jazuli (MUST: Journal of Mathematics Education, Science and Technology, 2022)
This study aims to: (1) produce interactive learning multimedia based on Articulate Storyline 3, which is feasible to increase motivation and achievement in science learning for grade VI students, and (2) describe the effectiveness of interactive learning multimedia based on Articulate Storyline 3 towards increasing students' motivation and achievement in science learning for grade VI students. This research is a type of development research. The results showed that: (1) interactive learning multimedia based on Articulate Storyline 3 met the eligibility criteria with a very decent category. (2) interactive learning multimedia based on Articulate Storyline 3 was effective in increasing student motivation and learning achievement.